Reproductive biology of Populus deltoides Bartr. - Dobhal, Sneha; Pokhriyal, Aman; Tripathi, Ritika; Kumar, Raj; Sharma, Samriti (Journal of Forests, 2023)
The detailed knowledge on the reproductive biology of plants is required for their successful cultivation and conservation. The reproductive characteristics of trees are required to assess the diversity patterns and community structure of the forests. Understanding the reproductive characteristics, such as, pollination, breeding systems, phenology, and floral biology of Populus deltoides is immensely important; because it is one the most important tree species in India. The review documented the physiological basis of the reproductive characteristics of poplar tree. Literature indicated that the dioecious species shows a regular flowering patternin both the male and female trees, and they produces flower (catkin) every year. In all the species, male flower buds bursted earlier than the vegetative bud, whereas, female flower buds bursted after the emergence of leaves. Unisexual flowering occurs between February and April in both male & female, and the dispersal of seeds reported in late May or early June. Most of the pollen grains exhibited reddish colour. The fruits are capsule shaped, splits into 3or 4 parts, and release cotton like seeds, which are viable for only a short period. Poplar mostly regenerates from seed under natural conditions, but are also capable of asexual or vegetative reproduction under artificial conditions. The male and female plant produces a significant number of hybrids seeds; resulting in an excellent growth of the plants. The species displayed cross-pollination characteristics. The information documented in the current literature will be quite useful to understand the reproductive characteristics of the Populus deltoides.